Transcriptome Analysis of Sucrose Metabolism during Bulb Swelling and Development in Onion (Allium cepa L.) - Zhang, Chunsha; Zhang, Hongwei; Zhan, Zongxiang; Liu, Bingjiang; Chen, Zhentai; Liang, Yi (Frontiers in Plant Science, 2016)
Allium cepa L. is a widely cultivated and economically significant vegetable crop worldwide, with beneficial dietary and health-related properties, but its sucrose metabolism is still poorly understood. To analyze sucrose metabolism during bulb swelling, and the development of sweet taste in onion, a global transcriptome profile of onion bulbs was undertaken at three different developmental stages, using RNA-seq. A total of 79,376 unigenes, with a mean length of 678 bp, was obtained. In total, 7% of annotated Clusters of Orthologous Groups (COG) were involved in carbohydrate transport and metabolism. In the Kyoto Encyclopedia of Genes and Genomes (KEGG) database, “starch and sucrose metabolism” (147, 2.40%) constituted the primary metabolism pathway in the integrated library. The expression of sucrose transporter genes was greatest during the early-swelling stage, suggesting that sucrose transporters participated in sucrose metabolism mainly at an early stage of bulb development. A gene-expression analysis of the key enzymes of sucrose metabolism suggested that sucrose synthase, cell wall invertase and invertase were all likely to participate in the hydrolysis of sucrose, generating glucose and fructose. In addition, trehalose was hydrolyzed to two molecules of glucose by trehalase. From 15 to 40 days after swelling (DAS), both the glucose and fructose contents of bulbs increased, whereas the sucrose content decreased. The growth rate between 15 and 30 DAS was slower than that between 30 and 40 DAS, suggesting that the latter was a period of rapid expansion. The dataset generated by our transcriptome profiling will provide valuable information for further research.